Difficulties and Strategies in Producing English Writing Text: What do EFL Students’ Perceive? What do EFL Students’ Perceive? - Adelita, Devika; Kurniati, Eka Yuni; Daulay, Sholihatul Hamidah (Universitas Nahdatul Ulama Surabaya, 2023)
This study aimed to discover the EFL students' viewpoints on the difficulties they encountered when writing in English, as well as their strategies for overcoming these hurdles. This study was conducted on EFL students in a senior high school in Medan. This research involved the involvement of twenty-nine eleventh-graders. The researchers utilized a questionnaire and an interview to collect data following their research themes. The questionnaire aims to identify the barriers students face when writing in English. The questionnaire was sent using a Google form with closed-ended questions based on Bryne's (1988) categories and a five-point Likert scale (strongly agree, agree, neutral, disagree, and strongly disagree). Subsequently, an interview was conducted with a subset of participants (n = 5) specifically chosen to elicit further information about their strategies for overcoming writing difficulties. The interview was recorded using a cell phone by the researchers. Before data processing, the audio cassette was transcribed word-for-word. Thus, data collected with three instruments were analyzed using three approaches: frequency count for questionnaire data and content analysis for interview data. According to the findings, students encountered linguistic (grammar, vocabulary, language use, sentence construction) and psychological issues when composing English texts (lack of teacher instruction and feedback). There are no cognitive appearance issues. The students use mind mapping, translating materials from Indonesian to English, maintaining practice, and peer evaluation to overcome their writing difficulties. This research was expected to contribute to minimizing the difficulties experienced by students in writing English through the strategy revealed in this study